Risk assessment and monitoring programme of nitrates through vegetables in the Region of Valencia (Spain). (February 2017) - Quijano, Leyre; Yusà, Vicent; Font, Guillermina; McAllister, Claudia; Torres, Concepción; Pardo, Olga
Abstract: This study was carried out to determine current levels of nitrate in vegetables marketed in the Region of Valencia (Spain) and to estimate the toxicological risk associated with their intake. A total of 533 samples of seven vegetable species were studied. Nitrate levels were derived from the Valencia Region monitoring programme carried out from 2009 to 2013 and food consumption levels were taken from the first Valencia Food Consumption Survey, conducted in 2010. The exposure was estimated using a probabilistic approach and two scenarios were assumed for left-censored data: the lower-bound scenario, in which unquantified results (below the limit of quantification) were set to zero and the upper-bound scenario, in which unquantified results were set to the limit of quantification value. The exposure of the Valencia consumers to nitrate through the consumption of vegetable products appears to be relatively low. In the adult population (16–95 years) the P99.9 was 3.13 mg kg −1 body weight day −1 and 3.15 mg kg −1 body weight day −1 in the lower bound and upper bound scenario, respectively. On the other hand, for young people (6–15 years) the P99.9 of the exposure was 4.20 mg kg −1 body weight day −1 and 4.40 mg kg −1 body weight day −1 in the lower bound and upper bound scenario, respectively. The risk characterisation indicates that, under the upper bound scenario, 0.79% of adults and 1.39% of young people can exceed the Acceptable Daily Intake of nitrate. This percentage could join the vegetable extreme consumers (such as vegetarians) of vegetables. Overall, the estimated exposures to nitrate from vegetables are unlikely to result in appreciable health risks. Highlights: Nitrate levels in vegetables marketed in the Region of Valencia (Spain) are presented. Estimated exposures are unlikely to result in appreciable health risks control. Risk assessment contributes to improve food safety and to built public confidence in the way risk is assessed. Results demonstrate that the estimated exposures to nitrate from vegetables are unlikely to result in appreciable health risks control.